Using Pre-reading Strategies to Provide Historical Context in a Literature Course - Tisha Ulmer (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
Students find that pre-reading activities which help them make a personal transaction with the past also help them read earlier African American writers with intensified insight.